Utilization of Website and Interface to Help Raise the Brand Identity of Micro, Small and Medium Enterprises Owners - Nicholas, Bryan (VCD: Journal of Visual Communication Design, 2024)
In today's modern era, a website serves as a key aspect of a brand's identity, with ownership often signifying credibility for a business. However, many individuals still struggle to market their brand through a website, often due to complex website designs or limited accessibility. With numerous businesses emerging every year, a brand's identity and uniqueness are essential in standing out from competitors. To address this challenge, a solution has been developed, which is a website builder company that enhances brand identity. This research aims to explore the importance of websites for MSMEs (Micro, Small, and Medium Enterprises) and identify how they can be designed to be effective, focusing on simple interfaces and clear communication of essential information. The data was gathered through quantitative interviews with expert, extreme, and non-expert users. The findings suggest that owning a website is crucial for MSMEs, significantly influencing consumer behavior and that the design should be well-organized, visually appealing, and engaging.